Learning from Students: A Case Study of How Teachers Construct Their Knowledge of Content and Students - Yu-Ting Hung (National Taipei University of Education, 2019)
Under the impetus of the 12-Year Basic Education Curriculum, increasing attention has been devoted to its goals, which include taking initiative, engaging the public, and seeking the common good. Urgent discussion is required regarding the ways in which teachers should construct their knowledge of teaching content and students (KCS) to accommodate different multicultural subjects in class and allow for individualized learning in order to achieve the goals above. This research entailed a two-year case study that delved deep into a professional learning community (PLC) of teachers at a junior high school ninth grade class in New Taipei City. The researcher investigated how teachers construct KCS through participatory observation, intensive interviews, and literature analyses. The study found that teachers ‟listened" to students' dialogues repeatedly throughout the learning process, and that both parties could gradually understand teaching and learning. The teachers connected all the information related to the students' learning context through a systematic process, which consisted of design, doing, diagnosis, and decision-making. Three main conclusions, which can hopefully serve as references for teachers, are as follows: 1) KCS can help teachers provide more accurate scaffold for learning; 2) Teachers must listen in order to outline KCS; and 3) evidence of student learning is an important medium for constructing KCS.